2020
DOI: 10.1021/acs.molpharmaceut.0c00727
|View full text |Cite
|
Sign up to set email alerts
|

Probenecid Increases the Concentration of 7-Chlorokynurenic Acid Derived from the Prodrug 4-Chlorokynurenine within the Prefrontal Cortex

Abstract: Recent advances in the understanding of depression have led to increasing interest in ketamine and the role that N-methyl-d-aspartate (NMDA) receptor inhibition plays in depression. l-4-Chlorokynurenine (4-Cl-KYN, AV-101), a prodrug, has shown promise as an antidepressant in preclinical studies, but this promise has not been realized in recent clinical trials. We sought to determine if transporters in the CNS could be playing a role in this clinical response. We used radiolabeled uptake assays and microdialysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…For this reason, in the main experiment, AV-101 was administered 1.5 h before and at the same time of L-Dopa to extend the duration of the effect of AV-101. A recent study also reported that 7-Cl-KYNA, which binds to the GlyB co-agonist site of NMDA-R, leaves the brain extracellular fluid via probenecid-sensitive organic anion transporters [ 24 ]. Indeed, the co-administration of probenecid with AV-101 increased the brain concentration of 7-Cl-KYNA [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For this reason, in the main experiment, AV-101 was administered 1.5 h before and at the same time of L-Dopa to extend the duration of the effect of AV-101. A recent study also reported that 7-Cl-KYNA, which binds to the GlyB co-agonist site of NMDA-R, leaves the brain extracellular fluid via probenecid-sensitive organic anion transporters [ 24 ]. Indeed, the co-administration of probenecid with AV-101 increased the brain concentration of 7-Cl-KYNA [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study also reported that 7-Cl-KYNA, which binds to the GlyB co-agonist site of NMDA-R, leaves the brain extracellular fluid via probenecid-sensitive organic anion transporters [ 24 ]. Indeed, the co-administration of probenecid with AV-101 increased the brain concentration of 7-Cl-KYNA [ 24 ]. Whether the co-administration of AV-101 and probenecid could have a beneficial effect on LID remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Colchicine prevents acute gout flares because of its anti‐inflammatory properties (Dalbeth et al, 2014 ), while allopurinol and febuxostat inhibit xanthine oxidase and thus reduce the synthesis of uric acid (UA) (Strilchuk et al, 2019 ), febuxostat and allopurinol lower the UA levels and attenuate the expression of an inflammatory marker, monocyte chemoattractant protein (MCP)‐1(Nakagomi et al, 2015 ). On the other hand, probenecid facilitates the excretion of uric acid by suppressing renal tubular transport (inhibits pannexin 1 channels) and blocking its reuptake (Patel et al, 2021 ). While, indomethacin inhibits the prostaglandins' synthesis by cyclooxygenase (COX) enzymes, thus reducing the amount of serum inflammatory mediators (Munjal & Allam, 2022 ).…”
Section: Introductionmentioning
confidence: 99%